Deletion of succinic semialdehyde dehydrogenase sad and chromosomal expression of phosphoenolpyruvate carboxylase as metabolic requirements for improved production of 2,4-dihydroxybutyric acid via malyl-P pathway using E. coli - Nguyen, T. A. Stefanie; Alkim, Ceren; Ihle, Nadine; Walther, Thomas; Frazão, Cláudio J. R. (Frontiers in Bioengineering and Biotechnology, 2025)
The fermentative production of the functional precursor 2,4-dihydroxybutyrate (DHB) enables sustainable synthesis of the methionine analogue hydroxy-4-(methylthio) butyrate, which is currently still produced from fossil fuels. In this work, we aimed to optimize the aerobic production of DHB from glucose through the synthetic malyl phosphate (MalP) pathway, which comprises the conversion of the natural TCA cycle intermediate malate into MalP and the subsequent reactions to yield malate semialdehyde (MalSA) and finally DHB. We first implemented the synthetic pathway in an engineered Escherichia coli strain previously reported to over-produce malate through the oxidative TCA cycle. However, DHB was only detected in trace amounts, while acetate and malate were secreted in high quantities. Subsequent construction of strains producing malate, but negligible amounts of acetate, revealed that an increased supply of malate alone is not sufficient for improved production of DHB. Instead, we discovered metabolic inefficiencies in the DHB pathway as we found that deleting the endogenous succinate semialdehyde dehydrogenase Sad, whose natural substrate is structurally similar to MalSA, strongly improved performance of the DHB pathway. Specifically, with the single knock-out of sad we could achieve a 3-fold increase in DHB production with a yield of 0.15 mol mol-1 compared to the wildtype host in shake flask experiments. With additional chromosomal expression of the mutant ppcK620S gene encoding the malate-insensitive phosphoenolpyruvate carboxylase under control of a weak constitutive promoter, we achieved a DHB yield of 0.22 mol mol-1, which corresponds to 17% of the maximal yield under aerobic conditions.